Analysis of elementary school EFL teachers' writing and discussion about critical incidents. (5th January 2021) - Chien, Chin-Wen
This paper aimed to explore elementary school English teachers' professional learning and reflective practice through writing and discussing critical incidents under the community of practice. The analysis and discussion of critical incidents were introduced to elementary school English teachers in order to foster their professional learning and reflective practice during their professional dialogue in the northwest city in Taiwan. Rather than discussing only the socio-cultural factors on discussing critical incidents among pre and in-service teachers in the current empirical studies, three research theories were used to analyse the 35 critical incidents, 19 interview, and six observations in terms of the levels of language and levels of thinking, types of critical incidents, and three modes of reflective thinking. This study has the following major findings. First, the majority of the critical incidents were related to students' behaviour. Second, these critical incidents were written and discussed using simple layperson description and traditional or personal preference. Next, English teachers' reflections were only at the technical level. Four suggestions are provided to foster a deeper level of reflection.